2023
DOI: 10.2147/ppa.s420545
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Lockdown on Glycemic, Weight, Blood Pressure Control and Medication Adherence in Patients with Type 2 Diabetes

Ruth Sim,
Chun Wie Chong,
Navin Kumar Loganadan
et al.

Abstract: Medication adherence profoundly affects blood glucose management in patients with type 2 diabetes. Measures to contain the COVID-19 pandemic have affected disease management and medication adherence, owing to limited access to healthcare facilities. This study aimed to examine the impact of the COVID-19 lockdown on adherence to glucose-lowering and lipid-lowering therapies (statins), and glycemic, weight, and systolic blood pressure control measures. A retrospective chart review was conducted one year pre- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A Japanese study addressing the same issue identified no clinically meaningful difference in PDC between periods before and during the pandemic, despite a temporary decline in physician visits ( Osawa et al, 2021 ). Finally, a study performed in Malesia observed a positive effect of lockdown on medication adherence with statins, which could be related to relaxed restrictions on medication prescriptions and larger quantities of medications supplied to patients due to the COVID lockdown, as well as the important role that telemedicine and mail-order pharmacies played during the pandemic period ( Sim et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study addressing the same issue identified no clinically meaningful difference in PDC between periods before and during the pandemic, despite a temporary decline in physician visits ( Osawa et al, 2021 ). Finally, a study performed in Malesia observed a positive effect of lockdown on medication adherence with statins, which could be related to relaxed restrictions on medication prescriptions and larger quantities of medications supplied to patients due to the COVID lockdown, as well as the important role that telemedicine and mail-order pharmacies played during the pandemic period ( Sim et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%